Polishing can reduce discoloration of the nanofiller composite resin filling due to the use of chlorhexidine - I Gusti Ketut Armiati (Makassar Dental Journal, 2020)
Nanofiller composite resin (NCR) restoration has a major problem, namely color changes. Polishing are factors that determi-ne color change and if accompanied by the use of mouthwash for a long time can cause more significant color changes. The 0.2% chlorhexidine gluconate mouthwash is a mouthwash that is often used in the community because it has low toxicity. However, using the chlorhexidine gluconate 0.2% mouthwash in the long term can cause more significant discoloration. This study is aimed to determine the difference between discoloration of polished and unpolished NCR on the soaking of 0.2% chlorhexidine gluconate mouthwash. This purely experimental research with a pretest and posttest with control group design, using 24 samples of premolar teeth prepared with class II cavity design and then filled with NCR. The samples were then di-vided into 4 treatment groups, namely polished and non-polished NCR, 0.2% chlorhexidine gluconate mouthwash and aqua-dest. Soaking was carried out 24 hours a day for 5 days in an incubator at 37ºC. Color changes of each group were measured using shade guide Vita Classical. The results were analyzed descriptively and the normality was tested by the Shapiro-Wilk and Levene's homogenity test with significance value of 0.05. Mann-Whitney for the different test. Based on the results of this study, it is concluded that the discoloration of the polished NCR was smaller than that was not polished on the soaking of chlorhexidine mouthwash 0.2%